PEMANFAATAN TEKNOLOGI MOLECULAR BREEDING DALAM PEMULIAAN KETAHANAN TANAMAN TERHADAP HAMA DAN PENYAKIT - Lukman, Rudi; Afifuddin, Ahmad; Hoerussalam, Hoerussalam (Jurnal Agroteknos, 2013)
Application of gene for gene hypothesis in breeding resistance to pests and disease should pay attention to genes and gene avirulen resistance of pathogens. The second aspect of  this  exploration  can  be  facilitated  by  molecular  breeding  technology.  In  addition, molecular marking can also be used to incorporate some resistance genes in an individual plant (gene pyramiding), a markup to the needs of cross-back (Marker Assisted Backcrossing), as well as experimental support for the detection of seed borne diseases. Rapid progress in the field of genomics has revealed some interesting phenomena about the genetics of microbes such as pathogenic effector, studies the genetic identity of an equality and diversity of microbial isolates that have not been explored. Better understanding of the mechanisms of pathogenicity and pathogen interaction between plants and will speed up the process of breeding for resistant plants. Keywords: Molecular Breeding, variability of pathogens, gene resistance